Overall stiffness evaluation and shape optimisation of a tensegric structure. (4th June 2010) - Chen, Pei-Shan
The present paper promotes a shape optimisation method for maximum overall stiffness of a tensegric structure, and reports a study on the overall stiffness of a tensile structure. General reduced gradient method is adopted for the shape optimisation, and a tensegric dome is taken as an example for the numerical demonstration. The results of numerical analysis show that the nodal displacements of the example decreases from 20%-30% compared to that of the initial shape.